Optimising the Mathematical Creative Thinking Process of Deporter's Learning Style Assisted E- Module Strukbar Based on Case Method - Isti Hidayah; Emy Sohilait; Isnarto; Kristina Wijayanti (Program Studi Tadris Matematika Universitas Islam Negeri (UIN) Salatiga, 2025)
The purpose of this research is (1) to identify the patterns of mathematical creative thinking processes based on DePorter's learning styles, and (2) to determine the improvement in mathematical creative abilities through learning assisted by the Strukbar E-module based on the Case Method. This research uses the Mixed Method with a Sequential Exploratory type. The research subjects are third-semester students of the 2024/2025 academic year in the Mathematics Education Study Program at STKIP Gotong Royong Masohi, Central Maluku, who are taking the Algebra Structure 1 course. In the qualitative research, the subjects consisted of three prospective teachers with DePorter's learning styles, while the quantitative research involved 26 participants. Data collection techniques include tests, DePorter learning style questionnaires, interviews, and documentation of prospective teachers' work. The research results show that DePorter's Visual, Auditory, and Kinesthetic learning styles each have their own advantages at the stages of mathematical creative thinking, from orientation, preparation, incubation, illumination, to verification. Moreover, the implementation of the Strukbar E-module based on the Case Method has been proven to significantly enhance the mathematical creative abilities of prospective teachers. These findings underscore the importance of teaching methods that align with individual learning styles and the use of digital technology in education.